World e-Parliament Conference 2007 and related meetings - Jane Bortnick Griffith; Jane Bortnick Griffith
This Report is a joint product of the United Nations Department of Economic and Social Affairs, the Inter-Parliamentary Union and the Association of Secretaries General of Parliaments. It provides a brief summary of the proceedings of the World e-Parliament Conference 2007 and related meetings held in Geneva in October 2007.